PTU-175 Value of PET-CT following neo-adjuvant chemotherapy to predict histological outcome in oesophageal adenocarcinoma. (28th May 2012) - Nasralla, D; Dwerryhouse, S; Hall, D; Searle, J; Barr, H; Lyburn, I
Abstract : Introduction: Repeat FDG-PET-CT imaging after neo-adjuvant chemotherapy (NAC) for oesophageal adenocarcinoma is controversial. Some authors claim repeat PET-CT enables clear management decisions to be made in carcinoma of the oesophagus 1 2 but this has been contradicted in a recent systematic review. 3 We reviewed patients with oesophageal adenocarcinoma who underwent pre and post NAC PET-CT to assess if metabolic response of the tumour correlated with operative histology findings. Methods: 27 patients with oesophageal adenocarcinoma underwent pre-and post-NAC PET-CT scan prior to oesophagectomy. The SUVmax pre and post NAC and the ratio of the final to initial SUVmax were calculated and compared with histological T and N stage, tumour area and differentiation. Results: No new metastatic lesions were discovered on post-NAC PET-CT. There was no significant difference between any of the parameters related to N stage. Initial SUVmax was greater for tumour stage T3-4 than for T0-2 [11.4 (SEM 1.6) vs 8.3 (1.4), p=0.05] and for poorly differentiated than for moderately differentiated tumours [11.5 (1.5) vs 8.0 (1.2), p=0.05]. Final SUVmax and the ratio of final to initial SUVmax were not significantly different for either T-stage or tumour differentiation. A correlation was seen between SUVmax and tumour area (0.39 vs 0.7). Conclusion: Initial SUVmax from PET-CT carried out before NAC is greater for tumours which are poorly differentiated than moderately differentiated, and for stage T3 or T4. The SUVmax from PET-CT studies carried out after the completion of NAC did not give additional information in this respect. The only area where it did offer potentially valuable information was correlation between tumour area and SUVmax, although this is unlikely to influence patient management. Post-NAC PET-CT did not predict histological outcome in our patients nor influence their management. Competing interests: None declared. References: 1. Lordick F, et al. PET to assess early metabolic response and to guide treatment of adenocarcinoma of the oesophagogastric junction: the MUNICON phase II trial. Lancet Oncol 2007;8 :797–805. 2. Bjorn LDM, et al. Neoadjuvant therapy of esophageal squamous cell carcinoma: response evaluation by PET-CT. Ann Surg 233:300–9. 3. Kwee R . Prediction of tumor response to neoadjuvant therapy in patients with esophageal cancer with use of 18 F FDG PET: a systematic review. Radiology 2010;254 .